Photo Based 3D Walkthrough - Yet, Lai Chan (Universiti Teknologi Petronas, 2006)
The objective of 'Photo Based 3D Walkthrough' is to understand how image-based rendering technology is used to create virtual environment and to develop aprototype system which is capable ofproviding real-time 3D walkthrough experience by solely using 2D images. Photo realism has always been an aim of computer graphics in virtual environment. Traditional graphics needs a great amount of works and time to construct a detailed 3D model andscene. Despite the tedious works in constructing the 3D models andscenes, a lot ofefforts need to beput in to render the constructed 3D models and scenes to enhance the level of realism. Traditional geometry-based rendering systems fall short ofsimulating the visual realism of a complex environment and are unable to capture and store a sampled representation ofa large environment with complex lighting and visibility effects. Thus, creating a virtual walkthrough ofa complex real-world environment remains one of the most challenging problems in computer graphics. Due to the various disadvantages of the traditional graphics and geometry-based rendering systems, image-based rendering (IBR) has been introduced recently to overcome the above problems. In this project, a research will be carried out to create anIBR virtual walkthrough by using only OpenGL and C++program without the use of any game engine or QuickTime VR function. Normal photographs (not panoramic photographs) are used as the source material in creating the virtual scene and keyboard is used asthe main navigation tool in the virtual environment. The quality ofthe virtual walkthrough prototype constructed isgood withjust a littlejerkiness.